How Have Chronic Pain Management Programs Progressed? A Mapping Review. Issue 7 (7th July 2019) - Lewis, Gwyn N.; Bean, Debbie; Mowat, Rebecca
Abstract: Objectives: Multidisciplinary pain management programs (PMPs) were established in the 1970s and are widely regarded as the gold standard management for people with chronic, noncancer pain. However, the recommended content of PMPs is not well described. The aim of the study was to determine the most common content and structure of inpatient PMPs, and describe how these have changed over time. Methods: A mapping review was performed of studies incorporating an inpatient PMP. Information on the content, format, structure, clinicians involved, and outcome measures was extracted. Publications were analyzed across 5 decades from the 1970s to the 2010s. Results: One hundred and four studies were included. All programs included physical therapy and psychology components, and most included education. While the physical therapy component did not change substantially, there was a shift from operant conditioning approaches to more cognitive behavioral methods over time, along with a reduction in active medication withdrawal and family involvement. Involvement of physical therapists, physicians, and psychologists remained high in the programs, but the inclusion of nurses and occupational therapists declined from the 2000s. The outcome measures revealed a shift to assessment of quality of life and general health. Discussion: Some of the content and format of PMPs has evolved over time, largely with developments in psychological approaches, and there is now more of a holistic approach to assessment.